The attitude of medical students towards HIV-infected people: fear or help? - A. A. Khryanin; O. V. Reshetnikov; T. A. Shpiks; V. K. Bocharova; M. V. Russkikh; I. O. Marinkin (Vestnik Dermatologii i Venerologii, 2019)
The study was conducted during the 2017–2018 period using the method of anonymous questionnaire. In total, 838 4-year-students from medical, pediatric, dental and medical-prophylactic departments participated in the study. Two questionnaires were used for the survey: an adapted version of the standard UNAIDS questionnaire and that based on V. V. Boyko’s methodology of diagnosing communicative tolerance. It is found that medical students do not condemn HIV-infected people, nor believe that people with a positive HIV status necessarily behave immorally, thus deserving this disease. Medical students show a high level of professional communicative tolerance and readiness to help these patients, although being afraid of getting the infection during medical manipulations. At the same time, a low level of awareness concerning a number of legal issues regarding HIV-infected patients has been established.